NATURAL MUTAGENESIS AS A POSSIBLE CAUSAL FACTOR FOR OCCURRENCE OF OBLIGATE EMBRYONIC DIAPAUSE IN MAMMALS (A HYPOTHESIS) - G. K. Isakova (Вавиловский журнал генетики и селекции)
The phenomenon of obligate embryonic diapause(delayed implantation) in mammals has been discovered more than150 years ago. Nevertheless, there is not the distinct idea on its origin and biological significance till now. Available data of cytogenetics, embryology, evolutionary morphology, and evolutionary ecology allow to believe that the obligatory stage of embryonic diapause might occur in single individuals with indifferent taxonomic groups in consequence of chromosome mutation caused by alteration in the environment and affected the expression of genes controlling the timing of embryogenesis.